Study on Premixed Combustion in a Diesel Engine with Ultra-multihole Nozzle - Xuelong Miao; Guiyang Zhang; Yusheng Ju; Xianyong Wang; Jian-hai Hong; Jin-bao Zheng; Xinqi Qiao; Zhen Huang (Journal of Combustion)
This study proposed a new low-temperature premixed combustion mode to achieve the simultaneous reduction of NOx and soot emissions in a volume production diesel engine of CA6DF by reconstructing key systems. Some developments of this diesel engine are as follows. A straight port and large diameter combustion chamber of a low compression ratio was developed. Inlet ports of a high induction swirl ratio were developed. A cooled EGR was developed. Especially, an ultra-multihole (UMH) nozzle was developed. It has two layers of injection holes and a large flow area. Two sprays of the upper and under layers meet in the space of the combustion chamber. The results showed that the operation range of this diesel engine to achieve the better low-temperature premixed combustion is as follows. The speed can cover from the idle speed to the rated speed. The load can reach to 50% of the full load of the corresponding external characteristics speed. The NOx and soot emissions of this operation range are simultaneously largely reduced, even by 80%–90% at most test cases, while keeping the brake-specific fuel consumption (BSFC) from being significantly deteriorated.